The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1590/fst.64820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone treatment on physicochemical parameters and ethylene biosynthesis inhibition in Guichang Kiwifruit

Abstract: To determine whether ozone can regulate fruit ripening and delay fruit aging, Kiwifruit (Actinidia deliciosa 'Guichang') was fumigated with different ozone concentrations (100 μL/L, 200 μL/L, 300 μL/L) for 3 h, stored at 1 °C and 85 ± 5% RH for three months, and then matured at 20 °C and 85% RH for 12 days. Compared with controls, the optimal concentration of ozone delayed kiwifruit ripening during cold storage by delaying the respiratory burst that precedes fruit decay. Consequently, fruit firmness, nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, some factors limit the use of non-thermal processing technologies in the industry, such as high investment costs and consumer concerns about food safety and so on (Rocha et al, 2022). Ozone treatment as a non-thermal technology is less costly and does not leave any residue on the products (Cao et al, 2022). Moreover, Ozone can act on many saturated and unsaturated organic matter, and effectively reduce the content of ethylene, ethanol and acetaldehyde in ripe fruits and vegetables (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some factors limit the use of non-thermal processing technologies in the industry, such as high investment costs and consumer concerns about food safety and so on (Rocha et al, 2022). Ozone treatment as a non-thermal technology is less costly and does not leave any residue on the products (Cao et al, 2022). Moreover, Ozone can act on many saturated and unsaturated organic matter, and effectively reduce the content of ethylene, ethanol and acetaldehyde in ripe fruits and vegetables (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ozone can significantly reduce the number of escherichia coli, yeast and mold on the surface of toona sinensis and maintain the storage quality (Lin et al, 2019). Ozone treatment is an effective method for post-harvest treatment of fruits and vegetables, which has achieved good preservation effect in fruits and vegetables such as kiwifruit (Cao et al, 2022), cantaloupe (Chen et al, 2020), button mushrooms (Wang et al, 2021b), toona sinensis (Lin et al, 2019), winter jujube (Zhang et al, 2022), etc. However, there are few reports on gaseous ozone treatment of fresh-cut water fennel.…”
Section: Introductionmentioning
confidence: 99%
“…While, limited by the feasibility of use, and different fungal responses, these two methods are not effective in grain storage (Santis et al, 2021;Mannaa & Kim, 2017). In recent years, numerous studies have shown that chlorine dioxide (ClO 2 ) and ozone (O 3 ), two strong oxidizing gases, can be used in gaseous or aqueous form to sanitize food and for food storage (Cao et al, 2018;Cao et al, 2022;Horvitz & Cantalejo, 2014;Lee et al, 2019;Park et al, 2021;Sun et al, 2017;Venta et al, 2010;Zhang et al, 2019). ClO 2 is a rapid and effective fungicide, which is active against bacteria, yeasts, and molds, and it is legally permitted in China to be used for fruit and vegetables sanitization in water (Li, 2010;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%